The Dipeptidyl Peptidase-4 Inhibitor Vildagliptin has the Capacity to Repair β-Cell Dysfunction and Insulin Resistance - Horie, A.; Tokuyama, Y.; Ishizuka, T.; Suzuki, Y.; Marumo, K.; Oshikiri, K.; Ide, K.; Sunaga, M.; Kanatsuka, A. (Hormone and Metabolic Research, 2014)
The aim of the present study was to determine whether the dipeptidyl peptidase (DPP)-4 inhibitor could repair pancreatic β-cell dysfunction and insulin resistance. Ten subjects with type 2 diabetes who had never received DPP-4 inhibitor treatment were enrolled in the study. Just before and 3 months after twice-daily administration of vildagliptin (50 mg tablets), insulin secretion and insulin sensitivity were estimated using 2-compartment model analysis of C-peptide kinetics and insulin-modified minimal model parameters, respectively. The first-phase insulin secretion (CS1) was determined as the sum of the C-peptide secretion rate (CSR) from 0 to 5 min (normal range 6.8–18.5 ng/ml/min). The whole-body insulin sensitivity index (SI) was calculated using a minimal model software program (normal range 2.6–7.6×10−4/min/μU/ml). After vildagliptin treatment, reductions in mean (± SE) HbA1c were noted (43.28±1.53 vs. 40.98±1.77 mmol/mol; p=0.019). Vildagliptin treatment increased the area under the curve for the C peptide reactivity (CPR) (AUCCPR; 26.66±5.15 vs. 33.02±6.12 ng/ml · 20 min; p=0.003) and CS1 (0.80±0.20 vs. 1.35±0.38 ng/ml/min; p=0.037) in response to an intravenous glucose load. Vildagliptin treatment significantly increased SI (0.46±0.27 vs. 1.21±0.48×10−4/min/μU/ml; p=0.037). The long-term administration of vildagliptin improved CS1 and Si suggesting that this drug has the capacity to repair impairments in pancreatic β-cell function and insulin resistance in type 2 diabetes.
Keywords: type 2 diabetes mellitus; glucagon-like peptide-1; first-phase insulin secretion; insulin-modified minimal model; insulin sensitivity